2020
DOI: 10.3389/fmicb.2020.569457
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Bacillus spp. as a Prospective Biological Tool for Control of Viral Diseases and Non-vector Leptinotarsa decemlineata Say. in Solanum tuberosum L.

Abstract: Viral diseases and their damage causing significant loss to economically important crops have increased by several folds during the last decade. All the conventional approaches are not able to eradicate the viral infection. Therefore, there is a need to look for efficient and eco-friendly viral disease-preventive measures. The genomic material of the majority of deleterious viruses of higher plants is RNA. One of the possible measures to control viruses is the use of ribonucleases (RNases), which can cleave RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 50 publications
1
43
0
Order By: Relevance
“…The study showed that treatment of potato plants with cells of the endophytic strain B. subtilis 26D promoted the restoration of plant growth after damage caused by CPBs. Previously, data on the alterations of plant growth by bacteria of the genus Bacillus under the influence of biotic and abiotic factors were summarized in the reviews [ 15 , 17 ]. However, investigations of the effect of PGPM on productivity of plants that were damaged by insect pests emphasize the direct insecticidal effect of strains under study [ 18 ] or their ability to induce plant resistance [ 16 ], but not their effect on the growth of damaged plants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study showed that treatment of potato plants with cells of the endophytic strain B. subtilis 26D promoted the restoration of plant growth after damage caused by CPBs. Previously, data on the alterations of plant growth by bacteria of the genus Bacillus under the influence of biotic and abiotic factors were summarized in the reviews [ 15 , 17 ]. However, investigations of the effect of PGPM on productivity of plants that were damaged by insect pests emphasize the direct insecticidal effect of strains under study [ 18 ] or their ability to induce plant resistance [ 16 ], but not their effect on the growth of damaged plants.…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment of plants with endophytes can be more advantageous than the cultivation of transgenic plants resistant to pathogens [ 14 ]. Implementing artificial plant microbiomes with PGPM that are capable of releasing their metabolites immediately in plant tissues can become a challenging alternative to conventional methods of plant protection and growth regulation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacteria: The gram-positive aerobic B. subtilis 26D (designated as 26D) strain from the collection of the Laboratory of Biochemistry of Plant Immunity of the Institute of Biochemistry and Genetics Ufa Federal Research Center Russian Academy of Sciences (UFRC RAS) (http://ibg.anrb.ru/wp-content/uploads/2019/04/Katalog-endofit.doc, accessed on 30 January 2022) was used. The B. subtilis 26D strain synthesizes the lipopeptide surfactin, exhibits proteolytic, antifungal, insecticidal and antiviral activities and also induces systemic resistance against pathogens and pests [24]. The isolate Bacillus sp.…”
Section: Research Objectsmentioning
confidence: 99%